Estimated daily intake of cadmium by children living in the city of Nis, Serbia - Nikic, Dragana; Stankovic, Aleksandra; Nikolic, Maja; Bogdanovic, Dragan; Petrovic, Branislav (The Turkish Journal of Pediatrics, 2009)
Cadmium is widely abundant in the air, water, soils and foodstuffs. Cadmium exposure and accumulation in the body start at a young age. Accumulation occurs in various tissues and organs, especially in the kidney cortex. This study was initiated to examine the total intake of cadmium among preschool children. The study group consisted of 275 children aged 1 to 6 years. Estimation of daily intake of cadmium was calculated using the recommended formula, which takes into consideration all the potential means of children's exposure to cadmium. The average daily cadmium intake in children aged 1 to 3 years was 1.06 microg/kg, while for the children aged 4 to 6 years, the average daily cadmium intake was 1.06 microg/kg. Biomonitoring methods were used to assess the effects of a contaminated environment on the children's health. Our research showed that children take in the highest amount of cadmium from food. It is estimated that by the age of 1-3 years, children have accumulated 1.31 mg of cadmium in the body, while those aged 4-6 years have accumulated 8.80 mg. The persistence in the environment of this metal requires a long-term move toward minimizing human exposure through environmental management and preservation of lower cadmium levels wherever possible.